Guest

the solution of dv + k v= -g is dt m A) v=c e -(k/m)t - m g k B)v=c – ( mg/k) e -(k/m)t C) v e -(k/m)t = c – (mg/k) ​D)v e -(k/m)t =c- (mg/k)

the solution of dvk v= -g  is
                       dt     m
 
A) v=c e-(k/m)t mg
                          k
B)v=c – (mg/k) e-(k/m)t 
C) v  e-(k/m)t  = c – (mg/k)
​D)v  e-(k/m)t  =c- (mg/k)
 

Grade:12

1 Answers

Vikas TU
14149 Points
3 years ago
Dear student 
Please type the question correctly ….........
You can also attach an image. …..........
Good Luck 

Think You Can Provide A Better Answer ?

ASK QUESTION

Get your questions answered by the expert for free